"Leapfrog Thermodynamics" among Binary Magnetic Phases Competing for Stability - Parks, T.C. (Journal of solid state chemistry, 1995)
Relative to Sm2Co7 plus Sm2Co17, SmCo5 is stable below 700 K and above 1000 K. Contrary to previous thinking, this is thermodynamically consistent. The free energies of formation of these phases seem to be marginal when estimated from data reported for the analogous compounds of other lanthanons. Above its Curie point at 713 K, Sm2Co7 is stabilized by its gain in entropy from magnetic disordering, so that SmCo5 loses the competition for stability. The Curie point of SmCo5 is 1020 K, above which SmCo5 experiences a similar gain in entropy, stabilizing it relative to Sm2Co7 plus Sm2Co17. Such "leapfrog thermodynamics" are especially evident in binary systems like Sm-Co, in which each discrete compound is subject to an order-disorder transition, for which the critical temperatures follow a monotonic trend across the phase diagram.